Learn Hadoop and Azure HDInsight basics this evening (in 2 hours). (Packt Publishing, 2022)
Be a part of the hands-on course for beginners to master the basics of the Hadoop Ecosystem. Take a tour of the concepts and fundamental understandings of Hadoop and implement its components in Azure through HDInsight. About This Video A short, hands-on yet comprehensive course on getting started with Hadoop and Azure HDInsight This module will prepare you to start learning big data in Azure Cloud using HDInsight All the requisite resource files come bundled with this course In Detail The Apache Hadoop is a framework that allows for the distributed processing of large data sets across clusters of computers using simple programming models. It is designed to scale up from single servers to thousands of machines, each offering local computation and storage. As numerous organizations move to big data, the demand for Hadoop professionals has been increasing massively. Thus, Hadoop is one of the most valuable skills to learn in today's world. In this course, you will start with learning a fundamental of the Hadoop Ecosystem and 3 main building blocks. Then, you will look at the challenges with Hadoop and how HDInsight solves these challenges. You will also learn cluster types, HDInsight architecture, and other important aspects of Azure HDInsight. After that, you will fetch data from the data lake, process it through Hive, and later will store data in SQL Server. Finally, you will see how HDInsight makes Hadoop easy, and go through a simple demo where you will fetch data from the data lake, process it through Hive, and later will store data in SQL Server. By the end of this course, you will have a solid understanding of the challenges that come with big data and how to solve them using Hadoop and HDInsight. You will be able to extract data from the data lake and process it through Hive and later store data in a SQL server. Audience This course is for beginners in Microsoft Azure Platform or anyone who is looking forward to starting their career as an Azure data engineer. If you are a Microsoft Azure data engineer, data scientist, database and BI developer, database administrator, data analyst, or similar profile, then this course will help you further in your professional venture. On-premises database-related profiles who want to learn how to implement Hadoop components in Azure Cloud can opt for this course. If you know basic T-SQL and database concepts, this course will be much easier to understand.